Competitividade da agricultura familiar na região central do Rio Grande do Sul: um estudo de caso utilizando a matriz SWOT - Gasperin, Adriano Roque de (2017)
The present dissertation aims to analyze the transaction costs and the strategic resources in family farms, in order to identify positive and negative aspects, which have a competitive impact for the farmer. Thus, the objective of this work is to evaluate the external and internal environment, referring to the farmer, in five productive activities in the municipality of Candelária, RS (tobacco, milk, rice, soy and corn). For the study of the external environment, the study used the theoretical approaches of the Transaction Cost Economics and theoretical basis of Resource Based View to analyze internal environment. In the external environment, the research question was related to transaction costs, coordination mechanisms and forms of governance, and their competitive impacts between productive activities and types of judicial nature of the buyers feedstock. The research problem related to the internal environment corresponded to identify the strategic resources and their competitive implications in productive activities. In order to operationalize and qualify the elements of external and internal environment the research considered the logic of SWOT analysis. Generally, the results show that maize productive activity has less interference from sources of transaction costs and coordination mechanisms compared to other productive activities studied. However, market governance is a threat to the maize producer. In other activities, hybrid governance is identified as positive for the farmer. All productive activities studied have assets specific, and in the productive activities of tobacco and milk are in greater numbers. Assets specific imply an increase in transaction costs, however, brand specificity (tobacco) and time specificity (rice and maize) may be opportunities, depending on the condition of the farmer. As to the judicial nature, cooperatives minimize uncertainties regarding the farmer and offer coordination mechanisms with more opportunities and fewer threats, thus providing an environment with more competitive advantages over other types of business. As for the internal environment, some strategic resources can reduce transaction costs, in rice production, resource - drying and storage - can alleviate the threat from opportunistic behavior of customers. However, in rice and maize activities, resources that generate competitive advantages (drying and storage) can allow the use of opportunities arising from transaction costs (time specificity). Additionally, for soy, the resource - technology used - minimizes the threats generate from the assets specificity (time and physical specificity). Thereby, strategic resources can be an instrument to reduce transaction costs by the farmer.